The High Pressure Inside Aerosol Particles Enhances Photochemical Reactions of Biomass Burning Compounds - Dubois, Clément; Perrier, Sébastien; George, Christian; Riva, Matthieu (ACS earth and space chemistry, 2024)
Ultrafine aerosols (d < 100 nm) are the most abundant particles in the atmosphere with strong implications for climate and air quality. Their formation and evolution remain a subject of significant uncertainty. Recently, the implication of a fundamental and hitherto unconsidered characteristic of ultrafine aerosols has been highlighted: the Young–Laplace pressure. Here, the photochemical reaction of vanillin, a proxy for biomass burning compounds, under various high pressures was investigated. Using high-resolution mass spectrometry and UV–visible spectroscopy, we demonstrated that vanillin photodegradation was faster by ∼40% under high pressures typical of atmospheric nanoparticles. Chemical characterization shows that dimer formation, ring-opening, and cleavage processes were greatly favored (i.e., up to ∼250%) at high pressures. While the formation of light-absorbing compounds appears to be nonaffected, their decomposition through photooxidative processes was shown to be 50% faster at high pressures. This study establishes that the high pressure inside nanometric-sized aerosols has to be considered as a key property that can significantly impact photochemical processes involved in aerosol growth and aging.